'Unreliable memoirs': geography at Aberdeen 1960–2002. (2nd October 2019) - Chapman, Keith; Gemmell, Alastair M. D.
ABSTRACT: We have drawn upon our combined experience of almost 90 years to reflect upon the changing life and times of the Department of Geography at the University of Aberdeen from the 1960s to the start of the new millennium. Our account is divided into four sections corresponding to the successive decades from the 1960s, when AMDG was an undergraduate student in the Department, to the 1990s, when KC was Head of Department (HoD). This chronological approach is not simply an arbitrary and convenient framework; the character and concerns of each of these periods were very different. These differences reflect the complex interactions between essentially 'local' institutional circumstances and the wider policy environment, affecting all universities, associated with the shift from an elitist to a mass higher education system.